Factors that are related to adherence and care seeking for hypertension treatments in individuals on antiretroviral therapy in central Malawi - Phiri, Khumbo (2021)
Hypertension which occurs in 1 out of 3 adults is the most common non communicable disease (NCD) in Malawi. Despite its high prevalence, treatment coverage for hypertension is low. Low rates of health seeking behavior, unhealthy lifestyles and poor access to health care remain key challenges to the prevention, control and management of hypertension. The objective of the study is to identify the factors related to care seeking for hypertension among adults on antiretroviral therapy (ART). We conducted in-depth interviews with 30 individuals who are 18 years or older, on ART who also have hypertension. Interview questions focused on challenges and enablers to care seeking for hypertension and patients’ perceived risks and benefits to health care utilization for hypertension. Andersen’s behavior model for health services utilization (BMHU) was used as an organizing framework. Data were analyzed through constant comparison methods using Atlas.ti 8, applying both deductive and inductive techniques using a modified grounded theory approach. The results are presented based on common themes within the BMHU framework. The most common barriers for care seeking, adherence to medication and general management of hypertension included financial challenges due to poor health and weakened physical ability and medication side effects. At the health system level, lack of integrated care, lack of available hypertension medications, long wait times, and poor quality of care were the major challenges to care seeking. Respondents perceived risks of hypertension influenced their decision to start or stay on hypertension treatment. Knowledge about the benefits of treating hypertension encouraged individuals to properly manage their hypertension, despite barriers to care.Among our participants on ART with hypertension there was a high level of knowledge about the risks of hypertension and high motivation for treatment, but individuals faced significant challenges to care seeking. Patient barriers could be reduced through integration of hypertension treatment within ART clinics, free or low cost access to antihypertensives, improvements in the supply chain for hypertension medication, and support services (counseling or other) for patients with multi-morbidity.